Islam and religious change in Pakistan Sufis and Ulema in 20th century South Asia - Sumbal, Saadia (New York : Routledge, 2021)
"This book examines the history of and the contestations on Islam and the nature of religious change in 20th century Pakistan, focusing in particular on movements of Islamic reform and revival. The book brings the different facets of Islam together within the confines of a single study and connects various strands of Islam from macro to micro level. Using a rich corpus of Urdu and Arabic material including biographical accounts, Sufi discourses (malfuzat), letter collections and polemics, the author investigates how various facets of Islam particularly Islamic reformism and shrine-oriented traditions interacted with one another and with post-colonial state of Pakistan, created in the name of Islam. Focusing on the district Mianwali of Pakistani south-western Punjab, the book demonstrates how reformist ideas could find space to permeate effectively only after accommodating sufi thoughts and practices, the text-based religious identity coalesced with overlapped traditional religious rituals and practices. The author argues that reformist Islam did establish itself but could not displace shrine-based religiosity. Reformist Islam had to come to terms with the Sufi ethos to make itself acceptable. Challenging the approach to view the contestation between reformist and shrine-oriented Islam through the lens of binaries modern/traditional and moderate/extremist, this book makes an important contribution to the field of South Asian religion and Islam in modern South Asia"--
Introduction -- 1. Migrant Sufis and Rooting of Islam (ca. 1600-1900) -- 2. Islamic Reformism and Shrine-based Religiosity: A Dialectical Identity -- 3. Reformist Islam: Emergence of Communal Identities and Politics of Nationalism -- 4. Sectarianism and The Politics of Religious Exclusion -- 5. Assertion of Deobandi Identity and Widening of Sectarian Cleavage -- Conclusion -- Appendixes -- Bibliography -- Glossary -- Index.
Keywords: Islam -- Pakistan -- History -- 20th century; Sufism -- Pakistan -- History -- 20th century; Ulama -- Pakistan; SOCIAL SCIENCE / Ethnic Studies / General